A Case Report on Fahr’s Syndrome: Complex Presentation and Diagnostic Challenges - Dhaka, Sandhya; Jha, Deepak; Masood, Iram; Pawar, Vikas; Bedarkar, Shivani (Indian Journal of Pharmacy Practice)
Fahr's syndrome, an exceedingly rare neurogenetic disorder characterized by abnormal bilateral calcium deposition in the brain, primarily affects individuals in their 30s and 40s. This case report details a 55-year-old female with Fahr's syndrome presenting generalized seizures, extrapyramidal features, and left basal ganglia calcification. Despite months of sodium valproate treatment, seizures persisted. Initial assessment revealed elevated blood pressure, hypocalcemia, hyperglycemia, and positive Chvostek's sign. Intravenous calcium, midazolam, and nitroglycerin were administered, resulting in significant improvement. Laboratory investigations highlighted metabolic abnormalities and radiological examination confirmed symmetrical bilateral basal ganglia calcification, gliotic changes, and mild cerebral atrophy. The case aligns with Fahr's syndrome, emphasizing the need for close monitoring and tailored therapeutic interventions to manage its diverse clinical spectrum and potential complications. The pathophysiology, linked to calcium and phosphorus imbalances, underscores the complex nature of this disorder. Comprehensive understanding and diligent care are crucial for effectively addressing Fahr's syndrome, given its rarity and the challenges associated with its diagnosis and management.
Keywords: Fahr's syndrome; Basal ganglia calcification; Generalized seizures; Neurogenetic disorder; Metabolic abnormalities